The price-setting behavior of banks: An analysis of open-end leverage certificates on the German market - Entrop, Oliver; Scholz, Hendrik; Wilkens, Marco (Journal of Banking & Finance, 2009)
This paper presents the first analysis of open-end leverage certificates on the German market. The major innovations of these certificates are twofold. First, issuers announce a price-setting formula according to which they are willing to buy and sell the certificates over time. Second, the product’s lifetime is potentially endless. Our main findings are that the price-setting formula is (i) designed to strongly favor the issuer and (ii) is consistent with the main outcome of the ‘life cycle hypothesis’ for structured financial products [Stoimenov, P.A., Wilkens, S., 2005. Are structured products ‘fairly’ priced? An analysis of the German market for equity-linked instruments. Journal of Banking and Finance 29, 2971–2993]. (iii) This holds for different product features and also in the presence of issuers’ credit risk and jump risk in the underlying.